Monitoring of left ventricular assist device implantation and set-up with miniaturized transoesophageal echocardiography: Initial experience at La Pitié-Salpêtrière Hospital and possible application fields. Issue 8 (1st December 2016) - Bouabdallaoui, Nadia; Lebreton, Guillaume; Demondion, Pierre; Charfeddine, Ahmed; Leprince, Pascal
Abstract: Background: Left ventricular assist devices are valuable options for mechanical circulatory support in patients with severe heart failure as a bridge to cardiac transplantation, to recovery, or as destination therapy. Transoesophageal echocardiography plays a key role in the management of left ventricular assist device patients; either in guiding the device implantation or in post-operative haemodynamic assessment. The aim of this observational study is to investigate the usefulness of a miniaturized transoesophageal echocardiography probe designed for continuous haemodynamic monitoring (haemodynamic transoesophageal echocardiography; ImaCor, Garden City, NY) in the haemodynamic assessment of patients undergoing left ventricular assist device implantation. Methods: Between June 2014 and September 2014, seven consecutive patients underwent left ventricular assist device implantation for severe heart failure. A haemodynamic transoesophageal echocardiography probe was used for continuous haemodynamic monitoring in the pre-, intra- and post-operative periods. All procedures were performed by haemodynamic transoesophageal echocardiography-trained physicians. Results: All data were recorded and used without need of a further haemodynamic device. The average number of haemodynamic assessments in each patient was 5.3. The average number of haemodynamic assessments leading to therapeutic changes in each patient was 2.6. The mean duration of haemodynamic transoesophageal echocardiography probe insertion was approximately 20 hours (9 hours – 72 hours). No device complications were noticed during this period. Conclusions: This observation suggests that haemodynamic monitoring using the haemodynamic transoesophageal echocardiography system in left ventricular assist device patients is feasible after a brief training period. The overall impact of haemodynamic transoesophageal echocardiography use in these patients is yet to be determined and further studies are still required.